"Pappaseng and Deep Learning: A Perspective on Strengthening Student Character through Local Wisdom" - Syamsudduha, Syamsudduha; Ita Rosvita; Muhammad Ilham (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to examine the integration of local wisdom values from Pappaseng of the Bugis tradition through a deep learning approach to support the strengthening of students’ character. Pappaseng contains moral messages such as work ethic (reso), mutual cooperation, solidarity, religiosity, scholarship, and health. These messages are relevant to the principles (outcomes) embedded within deep learning. The study investigates whether the values of Pappaseng align with the dimensions of deep learning, which emphasize meaningful understanding, self-reflection, the development of social attitudes, and the connection of knowledge to real life contexts using a qualitative methodology based on literature review. The findings indicate that integrating these two concepts can lead to a more holistic learning process that combines mastery of knowledge, critical thinking skills, strong moral formation, and a solid cultural identity. This synergy has the potential to cultivate a generation that is intellectually capable, honest, resilient in the face of global changes, and beneficial to society.